A theoretical guide for the integration of the clinical internships for interns and clinical tutors in the mental health professions - Dall'Aglio, Raffaella; Virga, Mariano; Catellani, Sara; Coriani, Sandra; Nasi, Anna Maria; Galeazzi, Gian Maria; Pingani, Luca (Acta Biomedica Atenei Parmensis, 2021)
The Degree Course in Psychiatric Rehabilitation Techniques from the University of Modena and Reggio Emilia (Italy) was established in 2001, with the aim of training health care workers with the competencies specified by the Ministerial Decree 182. Psychiatric Rehabilitation Technicians are graduated and qualified healthcare professionals who carry out rehabilitation and psychoeducational interventions with persons having mental health problems and related disabilities. The integration between theoretical knowledge and practical experimentation builds up professional competence and allows it to develop and consolidate profession-specific skills and to experiment with pre-socialisation for the job arena. Over the years, the necessity to develop an evaluation form of internship experience has arisen to provide detail in respect to the certification of competencies gained during the clinical internship, considering the complexity of the clinical services and of the service users that interns make contact with. The aim of this paper is to describe the Guide to Clinical Internships for Interns and Clinical Tutors, a useful instrument for interns to optimize their study and clinical internship experience for training as future mental health professionals with specific competencies in the technical and relational field and developing critical ability and autonomy of judgement.